2020
DOI: 10.1002/ijc.33158
|View full text |Cite
|
Sign up to set email alerts
|

VacA genotypes and cagA‐EPIYA‐C motifs of Helicobacter pylori and gastric histopathological lesions

Abstract: Helicobacter pylori infection induces inflammation of the gastric mucosa, which may progress to precancerous lesions and gastric cancer. The gastric histo-pathological damages may be associated with some virulence genes of the bacterium, notably vacA and cagA genes. To establish correlations between these genes and the lesions, biopsies from 1303 adults consenting patients that were previously analyzed by PCR to characterize vacA-s vacA-m, vacA-i regions and cagA 3 0 region polymorphism, were used. The highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…The vacA subtypes: s1as1bm2, s2 m2 and m2, s1bm2 were significantly correlated to gastritis, whereas, subtypes s1am1 , s1am2 , m1 were significantly associated with gastric and duodenal ulcers ( 12 ). A present study reveals a significant association between the strains carrying the vacA m1 alleles and intestinal metaplasia in addition to gastric cancer ( 61 ). In this study, the vacA genotypes of the 85 H. pylori strains were diverse, but s1c/m1b (30.6%) and s1c/m2 (41.2%) were the dominant genotypes and the most frequent combination in chronic non-atrophic gastritis.…”
Section: Discussionmentioning
confidence: 53%
“…The vacA subtypes: s1as1bm2, s2 m2 and m2, s1bm2 were significantly correlated to gastritis, whereas, subtypes s1am1 , s1am2 , m1 were significantly associated with gastric and duodenal ulcers ( 12 ). A present study reveals a significant association between the strains carrying the vacA m1 alleles and intestinal metaplasia in addition to gastric cancer ( 61 ). In this study, the vacA genotypes of the 85 H. pylori strains were diverse, but s1c/m1b (30.6%) and s1c/m2 (41.2%) were the dominant genotypes and the most frequent combination in chronic non-atrophic gastritis.…”
Section: Discussionmentioning
confidence: 53%
“…H. pylori is a major risk factor for gastric cancer [ 98 ]. Studies have shown that approximately 2% ~ 3% of people infected with H. pylori eventually develop gastric cancer [ 99 ]. Studies have also shown that autophagy can be induced by the concerted action of H. pylori and virulence factors in tumor cells [ 100 ].…”
Section: Crosstalk Between Microbiota and Autophagy In Cancer Developmentmentioning
confidence: 99%
“…6 Chronic infection with H. pylori exposes the gastric mucosa to various bacterial components such as lipopolysaccharide (LPS), outer membrane vesicles (OMVs), and toxic proteins. [7][8][9][10][11] The LPS from H. pylori can impair the expression of EGF and trigger the phosphorylation of STAT3, leading to gastric mucosal damage and chronic inflammation. 9 The OMVs produced by H. pylori can stimulate the mTOR signaling pathway to promote cell proliferation and carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%